Prostatic Carcinoma With Aberrant Expression of p63: A Case Report and Review of the Literature. Issue 3 (May 2020) - Paulk, Adina; McCool, Isaac; Sesterhenn, Isabell; Burke, Allen
Abstract : Abstract: Prostatic carcinoma with aberrant expression of p63 is a rare variant of prostate cancer, which represents a potential diagnostic pitfall, as it may be easily confused with either benign prostatic glands or high-grade prostatic carcinoma. In studies of radical prostatectomies, these tumors appear to behave like low-grade carcinomas despite frequent poorly formed architecture. We report a case of prostatic carcinoma with aberrant expression of p63 with a review of the literature and helpful features in the differential diagnosis of this entity.